Profesionalisme Guru Akuntansi Pasca Sertifikasi - Muhammad Ansori; Sandy Arief; S Sukirno (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2017)
This study will be discussed related to the professionalism of teachers after certification, the efforts made to develop the professionalism of teachers, and the impact of certification policy on the quality of education. This research subject is accounting certified teacher with a population of 7 informants, and informants are the principal supporter and 3 learners. This research method is a descriptive qualitative approach, with this type of case studies. Collecting data using the model interviews, observation, and documentation. Data analysis techniques to 1) Data collection 2) reduction of data 3) data presentation 4) conclusion / verification. The results showed that 1) accounting certified teachers have a good level of professionalism. The teacher can understand the characteristics of students, mastering both subject areas of a scientific or educational field, is able to organize teaching well, mastering the material in depth, mastering the technology and professionalism are able to develop in a sustainable manner. 2) the efforts of teachers to develop professionalism is with workshops, seminars, training, training, writing books, looking for a new regulation, to follow the teacher association continues studies to improve the qualifications and buy gadgets as supporting tools in learning. 3) certification of a positive impact on the quality of education. It is suggested that could be given to teachers, namely that the purpose of the certification is not to get professional allowance alone, but that teachers can master the competence of teachers well and make teachers more professional in carrying out his profession. Professional allowances simply as a consequence of this capability.